Crossover from the weak to strong-field behavior of the longitudinal interlayer magnetoresistance in quasi-two-dimensional conductors: Магнитоквантовые осцилляции - Grigoriev, A.D.; Grigoriev, P.D. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2017)
We investigate the monotonic growth of longitudinal interlayer magnetoresistance R̅zz(Bz), analyticallyand numerically in the self-consistent Born approximation. We show that in a weak magnetic field the monotonic part of R̅zz(Bz) is almost constant and starts to grow only above the crossover field Bc, when the Landau levels (LL) become isolated, i.e., when the LL separation becomes greater than the LL broadening. In higher field Bz >> Bc, R̅zz(Bz) µ Bz1/2 in agreement with previous works.